Ecology of parasitism of nestling Eurasian eagle-owls (Bubo bubo) by leucocytozoon ziemanni - Ortego, Joaquín; Espada, Francisco; Baquero, Rocío A. (Raptor Research Foundation, 2007)
The study of blood parasites in birds has increased in the past two decades as a result of their influence on several components of host fitness and evolution. However, the ecology of the interaction between blood parasites and their hosts is still poorly known. For example, we know relatively little about the temporal stability of blood parasite communities (see Fallon et al. 2004 and references therein) and, to our knowledge, data on interannual stability of infections in successive offspring cohorts for long-lived territorial bird species are not currently available. In addition, the amount of time between nestling hatching and the appearance of parasite gametocytes in blood samples from chicks is unknown for most bird species and for most blood parasites in the wild (Krone et al. 2001). Furthermore, the chick age at the time of sampling may be relevant to explanations of some recorded absences of blood parasites, such that hypotheses to justify such absences (e.g., elevated host immunocompetence or the absence of vectors for hemoparasite transmission) might be incorrect in some cases (Martínez-Abraín et al. 2004). Although several aspects of Eurasian Eagle-Owl (Bubo bubo) ecology have been studied, most data on blood parasites infecting this species are relatively sparse (Krone et al. 2001, Ortego and Espada 2007). Here, we record blood parasites of nestling eagle-owls in a population from central Spain; estimate the age at which infections become first patent; estimate baseline values of prevalence and intensity of infection in the study population and analyze the relationship between these variables and estimates of fledgling quality and availability of adequate prey; and explore whether the parasitism status is consistent between two successive broods from the same owl pair. During this work the first author was supported by a predoctoral fellowship from the Junta de Comunidades de Castilla-La Mancha and the European Social Fund. Peer reviewed